KAJIAN YURIDIS TERHADAP PEMBERIAN KREDIT MIKRO SUMUT SEJAHTERA II BERDASARKAN UNDANG-UNDANG NO. 20 TAHUN 2008 TENTANG USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) (STUDI PADA PT. BANK SUMUT) - ANASTASIA ADINDA (University of North Sumatera, 2013)
ABSTRAK : Micro, Small and Middle Business (Law No 20 of 2008) provides one of the economic policy of the government to help the people of funding disbursed by the financial institution according to the regulation of Bank Indonesia No 14/22/PBI/2012 about credit or financing by commercial bank and Technical Assistance for Development of Micro, Small and Middle Business as well as non-bank financial institutions in the form of loans (credit), therefore the Micro, Small and Middle Business also have a strategic role in the fight against poverty. As for the tittle of the scription is “Judicial Study Against Giving The North Sumatera Property Micro Credit II According to the Law No 20 of 2008 about Micro, Small and Middle Business (Studies in PT. Bank Sumut)”, with problem such as what are the types of loans for Micro, Small and Middle Business in the PT. Bank Sumut, how the requirements and the process of North Sumatera Prosperity Micro Credit II in PT. Bank Sumut as well as how the rights and obligations of the parties in the provision of North Sumatera Prosperity Micro Credit II in PT. Bank Sumut. The method applied in this writing is a normative law study and using secondary data that consist of primary, secondary, tertiary legal materials. The data collected through library research and supported by data obtained through field research at PT. Bank Sumut using a qualitative approach to produce a descriptive. The results in this research scription concludes that the types of loans at PT. Bank Sumut in accordance with the types of credit in general, such as Public Credit, Credit Installment Others (KAL), Credit Sumut Prosperous I (SS I) and North Sumatera Prosperity Micro Credit II (SS II). The requirements to get the loans from North Sumatera Prosperity Micro Credit II is to make a written request, a copy of identity, have a business license from authorities (Ward/Village Head, Head of Market), photo business location and a place to stay, a copy of proof of collateral/insurance, and savings accounts. Stage loans consist of marketing and promotion stage, the stage of credit analysis, loan disbursement stage, and the stage of supervision and monitoring. Rights of borrowers are receiving loans disbursed a sum of money to the account debtors and receives back guarantee proof and other documents if the debt has been repaid, his duty is to pay installment over a specified time and pay all cost incurred for the implementation of the credit agreement. While the right of creditors are receiving appropiate time agreed installments and rceive proof of collateral/guarantees and other documents, while the obligation of creditors is pay binding, insurance credit and guarantee services, also giving back the evidence of collateral to the debtor if the debt has been repaid. Keywords : Credit, Micro, Small and Middle Business